Integrated Approach to Climate Change Adaptation - Gurung, Gehendra Bahadur; Bhandari, Dinanath (Journal of Forest and Livelihood, 2009)
Nepal's temperature is rising faster than the global average, with a higher rate in the Himalayas. Precipitation is becoming unpredictable, resulting in extremities. Poor people, who are dependent on the nature for their livelihoods, suffer from the impact of climate change and have to struggle hard to cope with it more than others. This paper summarizes the key insights drawn from a project carried out by Practical Action Nepal. The project appraised the community perception of climate change, its impact, the coping strategies adopted by the communities and the need for adaptation through participatory approach. Community?based adaptation activities were implemented to respond to the climate change and its impact. The lessons from the project indicated that climate change adaptation requires an integrated approach, including socio?economic development, environmental conservation and disaster risk reduction. Key words: Climate change, adaptation, vulnerability, watershed, sustainable development, integrated approach, disaster risk reduction, resilience Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.90-98